Systematic identification of long non‐coding RNAs during pollen development and fertilization in Brassica rapa. (16th August 2018) - Huang, Li; Dong, Heng; Zhou, Dong; Li, Ming; Liu, Yanhong; Zhang, Fang; Feng, Yaoyao; Yu, Dongliang; Lin, Sue; Cao, Jiashu
Summary: The importance of long non‐coding RNAs (lncRNAs) in plant development has been established, but a systematic analysis of lncRNAs expressed during pollen development and fertilization has been elusive. We performed a time series of RNA‐seq experiments at five developmental stages during pollen development and three different time points after pollination in Brassica rapa and identified 12 051 putative lncRNAs. A comprehensive view of dynamic lncRNA expression networks underpinning pollen development and fertilization was provided. B. rapa lncRNAs share many common characteristics of lncRNAs: relatively short length, low expression but specific in narrow time windows, and low evolutionary conservation. Gene modules and key lncRNAs regulating reproductive development such as exine formation were uncovered. Forty‐seven cis ‐acting lncRNAs and 451 trans ‐acting lncRNAs were revealed to be highly coexpressed with their target protein‐coding genes. Of particular importance are the discoveries of 14 lncRNAs that were highly coexpressed with 10 function‐known pollen‐associated coding genes. Fifteen lncRNAs were predicted as endogenous target mimics for 13 miRNAs, and two lncRNAs were proved to be functional target mimics for miR160 after experimental verification and shown to function in pollen development. Our study provides the systematic identification of lncRNAs during pollen development and fertilization in B. rapa and forms the foundation for future genetic, genomic, and evolutionary studies. Significance Statement: A time series of RNA‐seq experiments performed at five developmental stages during pollen development and three different time points after pollination in Brassica rapa provides a systematic identification of lncRNAs underlying pollen development and fertilization and forms the foundation for future genetic, genomic, and evolutionary studies of lncRNA in B. rapa as well as the function of lncRNAs in plant reproduction processes.